Trapped in vicious cycles: unraveling the health experiences and needs of adults living with socioeconomic insecurity - Sanne E. Verra; Maartje P. Poelman; Andrea L. Mudd; John de Wit; Carlijn B.M. Kamphuis (BMC, 2024)
Abstract Background This study explores the role of health in daily life and needs of Dutch adults (aged 25-49) experiencing one or more forms of socioeconomic insecurity stemming from their financial, housing, or employment situations. Methods 28 in-depth, semi-structured interviews were conducted in the Netherlands between October 2022 and February 2023. The interview guide included questions on participants' socioeconomic situation, the role of health in their daily lives, their health-related and broader needs. Data was interpreted using inductive reflexive thematic analysis. An advisory board consisting of adults with lived experiences of socioeconomic insecurity were consulted at multiple stages of the study (recruitment, interview guide, interpretation of results). Results Housing insecurity was widely experienced by participants. When asked about their financial situation, most participants expressed having no issues getting by, but later on, described vigorous efforts to minimize expenses. Participants' narratives revealed four key themes in relation to the role of health in daily life and associated needs. Firstly, socioeconomic insecurity led to diminished control over life, which led to the disruption of routines. Secondly, experiencing socioeconomic insecurity compelled participants to prioritize stress reduction and mental health improvement through calming yet potentially damaging coping mechanisms. Thirdly, those who experienced little opportunity for improvement in their already long-lasting socioeconomic insecurity shared a sense of stagnation in life, which co-occurred with stagnation in unhealthy routines and diminished well-being. Fourthly, participants expressed the need for someone to speak with. This support may help participants regain control over their lives, identify opportunities for more socioeconomic security, and focus on increased health and well-being. Conclusions This study sheds light on the challenges individuals face in dealing with socioeconomic insecurity, how it may affect their health, and their needs. Gaining perspective for improved socioeconomic security and having accessible professional support tailored to self-identified needs could have health-promoting effects for individuals living with socioeconomic insecurity. It is recommended to integrate professional support and assistance regarding social security into health policies and interventions. In future research, measures of financial strain should be adjusted to include the effort needed to get by.